2018
DOI: 10.18061/emr.v12i3-4.5814
|View full text |Cite
|
Sign up to set email alerts
|

Tapping to Carter: Mensural Determinacy in Complex Rhythmic Sequences

Abstract: The tapping paradigm has played an important role in formulating beat induction models. However, experimental studies that make use of actual music as source materials to investigate pulse finding mechanisms in complex rhythmic sequences are lacking. The present study proposes to use the concept of mensural determinacy, that is, the emergence of temporal expectations that may or may not be realized (Hasty, 1997), to explore the relative salience of an implied beat in two contrasting rhythmic sequences extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The second potential limitation is the gender effect. Due to the requirements and characteristics of artistic swimming, water polo, and drumming, the groups tested in the present study were not well balanced in gender, which might have influenced the results as suggested by Poudrier (2018). However, Aoki, Furuya, and Kinoshita (2005) and Au, Seah, Li, and Tan (2015) reported that gender had no influence on tapping ability.…”
Section: Discussionmentioning
confidence: 73%
“…The second potential limitation is the gender effect. Due to the requirements and characteristics of artistic swimming, water polo, and drumming, the groups tested in the present study were not well balanced in gender, which might have influenced the results as suggested by Poudrier (2018). However, Aoki, Furuya, and Kinoshita (2005) and Au, Seah, Li, and Tan (2015) reported that gender had no influence on tapping ability.…”
Section: Discussionmentioning
confidence: 73%
“…These findings may have been related to the magnitude of change used to create accents (e.g., Ellis & Jones, 2009, used two to five semitones differences, while the current study used only one semitone difference), a limitation that could be addressed in future experiments. On the other hand, there is also some evidence that the effect of different types of accents on beat perception may differ based on participants' musical expertise (Bouwer, Burgoyne, Odijk, Honing, & Grahn, 2018;Poudrier, 2017). In the current study, post hoc observations of grouping preferences based on native language and music training provide further evidence that basic auditory processes supporting pulse perception may be shaped by enculturation (Hannon, Soley, & Ullal, 2012;Iversen, Patel, & Ohgushi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a pulse clarity metric from empirical data, we looked into the annotator's tapping variability when tapping to the MIREX musical excerpts. We looked into the coefficient of variability (CV) of the inter-tap intervals of each annotator in each track [34]. The normalization of the coefficient of variability considers the variability with respect to the tapping rate selected by the listener.…”
Section: Plos Onementioning
confidence: 99%